Ecological aspects of the model of transformation of the eating behavior of students in Kazakhstan - Bayakhmetova Aliya; Bayakhmetova Lyazzat; Bayakhmetova Leyla; Daniyar Medet; Shchepkina Natalia (E3S Web of Conferences, 2023)
The UN Sustainable Development Goals and the Paris Climate Agreement are pushing the current generation to rethink and transform their behaviors. The importance of the research subject is due to the need for universities to implement the third mission and implement the University 4.0 model in response to emerging challenges of promoting sustainable development of society. The main purpose of the study is to assess the impact of students' dietary choices on students' academic achievements, taking into account environmental aspects. In the course of the study, a methodology based on a qualitative approach was used, including the development of questionnaires and the use of Chi-square statistics. The results obtained indicate that there is no relationship between students' academic performance and factors of rational nutrition. The analysis of the responses made it possible to conclude that there is an urgent need for universities to rethink the strategy and mechanisms for the implementation of the mission. It is necessary to give priority attention to the implementation of policies aimed at the formation of mechanisms for the transformation of students' eating behavior in order to achieve sustainable academic growth, taking into account environmental aspects.